Evaluasi Kesehatan dan Keselamatan Kerja dengan Metode HIRADC dan JSA Pada Proses Penyedotan Tinja - Reigeil, Keiyiko; Agung Rahmanto, Tuhu (Jurnal Serambi Engineering, 2025)
Instalasi Pengolahan Lumpur Tinja (IPLT) functions to treat domestic waste, such as faecal waste and restaurant waste. In Surabaya City, IPLT Keputih plays an important role in supporting environmental hygiene and public health so as not to pollute the environment and endanger public health. This study aims to evaluate the implementation of Occupational Safety and Health in the desludging process at IPLT Keputih in Surabaya. This process has a high level of risk for occupational accidents and health problems, so a systematic approach is needed in hazard identification and risk control. The method used is a combination of Job Safety Analysis (JSA) and Hazard Identification, Risk Assessment and Determining Control (HIRADC). Data collection techniques include field observations and literature studies. The results showed various potential hazards at each stage of the work, such as hose installation, suction, and cleaning. Control recommendations were obtained by installing warning signs, providing and using appropriate personal protective equipment, and regular OHS training.